2009
DOI: 10.1158/1078-0432.ccr-08-1791
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Breast Cancer with High-Resolution Oligonucleotide Comparative Genomic Hybridization Array

Abstract: Purpose: We used high-resolution oligonucleotide comparative genomic hybridization (CGH) arrays and matching gene expression array data to identify dysregulated genes and to classify breast cancers according to gene copy number anomalies. Experimental Design: DNA was extracted from 106 pretreatment fine needle aspirations of stage II-III breast cancers that received preoperative chemotherapy. CGH was done using Agilent Human 4 Â 44K arrays. Gene expression data generated with Affymetrix U133A gene chips was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
219
1
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(246 citation statements)
references
References 33 publications
21
219
1
5
Order By: Relevance
“…This is supported by observations in malignant melanoma, for example, where GLO1 copy number increase has low prevalence (2%) in early stages and high prevalence (80 -89%) in advanced stages [68,72,73]. Recent studies have found very high prevalence of GLO1 copy number increase also in gastric cancer (33%) [74] and in "triple negative" breast cancer lacking expression of oestrogen and progesterone receptors and epidermal growth factor receptor-2 genes (83%) [75]. These tumour types do not respond well to currently available chemotherapy; such tumours may be sensitive to permeable Glo1 inhibitor chemotherapy when available clinically [47].…”
Section: Discussionsupporting
confidence: 53%
“…This is supported by observations in malignant melanoma, for example, where GLO1 copy number increase has low prevalence (2%) in early stages and high prevalence (80 -89%) in advanced stages [68,72,73]. Recent studies have found very high prevalence of GLO1 copy number increase also in gastric cancer (33%) [74] and in "triple negative" breast cancer lacking expression of oestrogen and progesterone receptors and epidermal growth factor receptor-2 genes (83%) [75]. These tumour types do not respond well to currently available chemotherapy; such tumours may be sensitive to permeable Glo1 inhibitor chemotherapy when available clinically [47].…”
Section: Discussionsupporting
confidence: 53%
“…19 Therapeutic or prognostic significance of other frequently amplified genes such as cyclin D1 (CCND1) 20 or frequent loss of genes such as E-cadherin (CDH1) is less clear, and comparative genomic hybridization (CGH) studies have pointed to many more genes and chromosomal loci with potentially important copy number changes. [21][22][23] Nevertheless, no single gene copy number seems to completely explain prognosis or response to therapy of individual breast cancer patients. A simultaneous analysis of copy number changes of a variety of genes involved in prognosis and therapy response may thus be very useful for molecular profiling of individual breast cancer patients.…”
mentioning
confidence: 99%
“…Other genome-wide screens analyzing large groups of unselected breast cancer samples also showed that FGFR2 is rarely amplified (Adelaide et al 2007), and others did not find any amplifications or losses of FGFR2 (Andre et al 2009). However, FGFR2 was amplified in 4% of triplenegative breast cancer samples, whereas no amplification was found in other molecular subtypes.…”
Section: Fgfr2mentioning
confidence: 98%
“…Several studies have identified amplifications of FGFR1 in breast cancer (Chin et al 2006, Letessier et al 2006, Reis-Filho et al 2006, Elbauomy Elsheikh et al 2007, Marchio et al 2008, Andre et al 2009, Kadota et al 2009, Moelans et al 2010; Table 1). The percentage of FGFR1 amplifications found using different techniques ranges from 7.5 to 17%.…”
Section: Fgfr1mentioning
confidence: 99%
See 1 more Smart Citation